Penerapan Standar Kode Klasifikasi Arsip Pada Surat Dinas Di Rumah Sakit Provinsi Nusa Tenggara Barat - Indri Sari; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
The implementation of archival classification code standards is essential in ensuring effective records management within public institutions, including hospitals. This study aims to analyze the application of archival classification codes in managing official correspondence at a Provincial Hospital in West Nusa Tenggara. The research employs a descriptive qualitative method with a case study approach based on document analysis and archival practices. The results indicate that the application of classification codes has not been fully standardized, leading to inconsistencies in document organization and retrieval. From an archival perspective, proper classification systems enhance efficiency, accountability, and accessibility of records. However, limitations in human resources and lack of standardization guidelines hinder optimal implementation. This study highlights the importance of strengthening archival management systems to support administrative effectiveness and information governance.